Efektivitas Modul dan Film Pendek Check Up Diabetic Foot: Ipswch Touch Test dalam Meningkatkan Pengetahuan dan Ketrampilan Mendeteksi Neuropati Sensori Diabetes Mellitus Tenaga Kesehatan di Kabupaten Bima - Julhana, Julhana; Taufiqurrahman, Taufiqurrahman; Haris, Abdul; Rahmad, Indra (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Early detection of diabetic neuropathy is very important for patients with type 2 diabetes mellitus because early prevention can reduce morbidity and mortality. One of the examinations to detect diabetic neuropathy is the Ipswich Touch Test (IpTT). The purpose of this study was to determine the Effectiveness of the Diabetic Foot Check Up Module and Short Film: Ipswich Touch Test in Improving Knowledge and Skills in Detecting Sensory Neuropathy of Diabetes Mellitus Health Workers. The research method used was Quasi-experimental with a pre-test and post-test with control group design with a non-parametric Wilcoxon test to analyze knowledge and skills before and after treatment, a total of 60 respondents. A significant test result of 0.0001 was obtained for the intervention group, namely there was a difference in skills before and after treatment in the form of counseling with media in the form of short films, while in the control group a significant test result of 0.0001 was obtained, namely there was a difference in skills before and after treatment in the form of counseling with media in the form of modules with a significance level of 0.05 because p value <0.05. The results of the significant test were obtained at 0.0001 for the intervention group, namely there was a difference in knowledge before and after being given treatment in the form of counseling with media in the form of short films, while in the control group the results of the significant test were obtained at 0.0001, namely there was a difference in knowledge before and after being given treatment in the form of counseling with media in the form of modules with a significance level of 0.05 because the p value <0.05. The conclusion on the results of knowledge in the intervention group before being given intervention in the form of education, modules and short films was that they had good knowledge as much as 50% and after being given education they had good knowledge as much as 90% meaning that there was an increase in knowledge before and after being given intervention, meaning that there was an increase of 40%, while in the intervention group they had good skills 0%, enough 90%, less 10% after being given intervention there was a change to good as much as 83.3% meaning that there was a significant change before being given treatment and after being given treatment.